Preparation of Highly Stable and Photoluminescent Cadmium‐Free InP/GaP/ZnS Core/Shell Quantum Dots and Application to Quantitative Immunoassay. (31st January 2020) - Xu, Yanxia; Lv, Yanbing; Wu, Ruili; Shen, Huaibin; Yang, Huawei; Zhang, Han; Li, Jinjie; Li, Lin Song
Abstract: Indium phosphide (InP) quantum dots (QDs) are ideal substitutes for widely used cadmium‐based QDs and have great application prospects in biological fields due to their environmentally benign properties and human safety. However, the synthesis of InP core/shell QDs with biocompatibility, high quantum yield (QY), uniform particle size, and high stability is still a challenging subject. Herein, high quality (QY up to 72%) thick shell InP/GaP/ZnS core/shell QDs (12.8 ± 1.4 nm) are synthesized using multiple injections of shell precursor and extension of shell growth time, with GaP serving as the intermediate layer and 1‐octanethiol acting as the new S source. The thick shell InP/GaP/ZnS core/shell QDs still keep high QY and photostability after transfer into water. InP/GaP/ZnS core/shell QDs as fluorescence labels to establish QD‐based fluorescence‐linked immunosorbent assay (QD‐FLISA) for quantitative detection of C‐reactive protein (CRP), and a calibration curve is established between fluorescence intensity and CRP concentrations (range: 1–800 ng mL −1, correlation coefficient: R 2 = 0.9992). The limit of detection is 2.9 ng mL −1, which increases twofold compared to previously reported cadmium‐free QD‐based immunoassays. Thus, InP/GaP/ZnS core/shell QDs as a great promise fluorescence labeling material, provide a new route for cadmium‐free sensitive and specific immunoassays in biomedical fields. Abstract : Highly photostable thick shell InP/GaP/ZnS core/shell quantum dots (QDs) (12.8 ± 1.4 nm) with high quantum yield (QY) (72%) are successfully synthesized. Aqueous InP/GaP/ZnS QDs still keep high QY (more than 90%) and photostability. InP/GaP/ZnS QDs are used for C‐reactive protein quantitative detection. The limit of detection is 2.9 ng mL −1, which is twofold lower than the record values of cadmium‐free QD‐based immunoassays reported so far.